1993
DOI: 10.1039/c39930001201
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and stereo-selective ring opening of epoxides with amide cuprate reagents

Abstract: Amide cuprate reagents attack the less hindered carbon atom of epoxides to give 1,2-amino alcohols in good yields; this procedure is applied to the synthesis of an aziridine alcohol bearing a carborane framework which is a potentially useful 1 O B carrier for boron neutron capture therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The classical approach for the synthesis of β-aminoalcohols, involving nucleophilic opening of epoxides by amines requires heat treatment and requires an excess of amine. Several catalysts have been utilized in these reactions: montmorillonite [16], Ti(o-i-Pr) 4 [17], SmI 2 , [18] basic metal amides, [19] SmCl 3 [20], metal triflates such as Sn(OTf) 2 , Cu(OTf) 2 , LiOTf and Yb(OTf) 3 [21], ammonium decatungstocerate (IV) [22], RuCl 3 [23], zirconium (IV) chloride [24], cyclodextrins [25] and also CeCl 3 [26], silica-gel [27], alumina [28], ionic liquids [29], water [30] We have successfully used sulfated zirconia for Biginelli condensation reactions, [35] for the Paal Knorr reaction in the synthesis of tetrahydroindolone derivatives [36] and for the acylal protection and deprotection reactions [37]. In this paper we have synthesized, characterized and evaluated sulfated zirconia and SZ/MCM-41 in the oxirane opening with amines to obtain β-aminoalcohols under mild, solventless conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The classical approach for the synthesis of β-aminoalcohols, involving nucleophilic opening of epoxides by amines requires heat treatment and requires an excess of amine. Several catalysts have been utilized in these reactions: montmorillonite [16], Ti(o-i-Pr) 4 [17], SmI 2 , [18] basic metal amides, [19] SmCl 3 [20], metal triflates such as Sn(OTf) 2 , Cu(OTf) 2 , LiOTf and Yb(OTf) 3 [21], ammonium decatungstocerate (IV) [22], RuCl 3 [23], zirconium (IV) chloride [24], cyclodextrins [25] and also CeCl 3 [26], silica-gel [27], alumina [28], ionic liquids [29], water [30] We have successfully used sulfated zirconia for Biginelli condensation reactions, [35] for the Paal Knorr reaction in the synthesis of tetrahydroindolone derivatives [36] and for the acylal protection and deprotection reactions [37]. In this paper we have synthesized, characterized and evaluated sulfated zirconia and SZ/MCM-41 in the oxirane opening with amines to obtain β-aminoalcohols under mild, solventless conditions.…”
Section: Introductionmentioning
confidence: 99%
“…But deficiency of selectivity, requirement of excess amine and high temperature in the traditional method lead to the requirement of activation of epoxide by suitable catalyst to increase their impressibility to nucleophilic attack by amine. A preliminary study shows many methodologies had been reported earlier for the production of β‐amino alcohol derivatives, which includes the use of metal amides, transition metal halides, metal alkoxides, rare earth metal halides, metal triflates, alumina, alkali metal perchlorates, and silica under high pressure . The earlier reported synthetic methodologies have many disadvantages such as low yield of product, elevated temperature, expensive catalyst preparation pathway, moisture sensitive catalyst, and extended reaction time requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of new methods for the nucleophilic ring-opening of epoxides that work under mild conditions is of great importance. In this direction various Lewis acid promoters viz., metal halides [6][7][8][9], metal triflates [10][11][12][13], metal alkoxides [14], metal amides and triflamide [15][16][17], transition metal salts [18], hexafluoro-2-propanol under reflux (HFIP) [19], ionic liquid [20], zirconium sulfophenyl phosphonate [21], sulphated zirconia [22], silica [23], alumina/modified alumina [24,25] and montmorillonite clay were used as catalysts at room temperature/microwave irradiation [26] in the presence/absence of a solvent [27]. The reactions proceed smoothly to give the b-aminoalcohol in good to excellent yields.…”
Section: Introductionmentioning
confidence: 99%